Sorption Hysteresis of Light Hydrocarbons and Carbon Dioxide in Shale and Kerogen - Zhao, Huangjing; Lai, Zhiping; Firoozabadi, Abbas (Scientific reports, 2017)
We present adsorption and desorption isotherms of methane, ethane, propane, n -butane and iso -butane as well as carbon dioxide for two shales and isolated kerogens determined by a gravimetric method. The sorption measurements of two shales were performed at three different temperatures, 308.15, 323.15, and 338.15 K. For the isolated kerogens, the measurements were conducted at 338.15 K. Methane and ethane sorption isotherms were measured to 35 bar. Carbon dioxide sorption isotherms were studied to 30 bar. Due to the low vapor pressure at room temperature, the sorption isotherms of propane, n -butane and iso -butane were measured to 8, 2, and 2 bar, respectively. The adsorptions of propane, n -butane, and iso -butane were much higher than methane at the highest pressures where the measurements were conducted. The adsorption of n -butane was 10 times higher than methane by mole at 2 bar, followed by iso -butane and propane. Our data show significant adsorption hysteresis in ethane, propane, n -butane and iso -butane. The most pronounced hysteresis was found in n -butane and iso -butane. Significant hysteresis is attributed to the reversible structural changes of kerogens. Dissolution of adsorbates into organic matter may also affect the hysteresis. This is the first report of propane and butane sorption isotherms in shales.